Phylogenetic position and taxonomic assignment of Thlaspi aghricum PHDavis & K.Tan (Brassicaceae) - Firat, Mehmet; Ozudogru, Baris; Tarikahya-Hacioglu, Burcu; Bulbul, Ali Savas; Al-Shehbaz, Ihsan A.; Mummenhoff, Klaus (Magnolia Press, 2014)
A general review of the taxonomic status of Thlaspi past and present is given, and a critical evaluations of its segregates based on both morphological and molecular data are presented. ITS molecular phylogenetic study of Thlaspi aghricum and related species, as well as seed-coat morphology and anatomy strongly support the placement of the species in Noccaea. The new combination N. aghrica is proposed, and detailed description and distribution of the species are given.
Keywords: Brassicaceae; Cruciferae; Noccaea; Thlaspi; Seed